Equating CONTROL with ‘containment’: justifying the equation via animal Farm - Khazriyati Salehuddin (Penerbit UKM, 2004)
Unless they are expressed in more concrete manners, concepts, which are abstract in nature, are rather difficult to be appreciated. Thus, concepts such as CONTROL, are normally expressed using more concrete means, such as through the hierarchical and the front-back image schemas (Khazriyati 2002a & 2002b). Apart from the use of the word ‘control’ per se to manifest the concept, other metaphorical expressions such as in front of, behind and towards, are widely employed to realise the concept (ibid. & 2003). Though in terms of forms, those expressions are in no way similar to that of the word ‘control’, careful analysis via the cognitive semantics approach would enable one to be aware of the fact that the use of such expressions are not at all arbitrary in describing CONTROL. This paper looks at how the container image schema – one of the theoretical frameworks in cognitive semantics – is utilised to interpret the concept of CONTROL in Animal Farm.